On the policy of photovoltaic and diesel generation mix for an off-grid site: east malaysian perspectives - Ajan, Christopher W. (Elsevier Ltd., 2003)

(untitled)
The recent policy of the Malaysian government to promote use of renewable, especially photovoltaic, energy has warranted a feasibility study on supplementing diesel generation in off-grid sites by solar (photovoltaic) electricity to be done in the Malaysian context. This paper addresses the technical viability and economy of using a photovoltaic (PV) system to supplement an existing diesel generator-based supply in a typical secondary school located at an interior, off-grid and rural site of Sarawak state in East Malaysia. The findings of the present study, would therefore, help the Government with a realistic picture of the techno-economic aspects in implementing its vision regarding renewable energy. Presently, a 150kW diesel generator supplies electricity to the considered school. The study required simulation of the load sharing pattern of the PV-diesel hybrid system taking into account varied weather and insolation conditions of the chosen site. Also, the purchase price as well as the size of the supplementing PV system that would give the lowest life cycle cost have been determined. The PV system was considered in both forms, i.e. with and without battery back-up. It has been found that if the market price for purchasing a PV system would drop to RM 11.02/WP (Ringgit Malaysia; US$1.00=RM 3.80) i.e. US$2.90/WP, a 35>kWP PV system without battery back-up in conjunction with the diesel generator would be able to supply the selected school's demand at a marginally lower energy cost than the existing diesel-only system. With continuous research and developments, PV price would keep falling in the near future so that a PV-diesel hybrid system with a higher sized PV is expected to be economically more viable. The reported feasibility study can serve as a guideline for making similar studies in the context of another off-grid site.